Application of Gamma Rays Irradiation to Reduce Purine Base of Adenine and Hypoxanthine Content on Melinjo Chips (Gtnetum Gnemon L) - Nasrulloh, Nanang (Jurnal Ilmu Pangan dan Hasil Pertanian, 2019)
Background : Melinjo (Gnetum gnemon L) chips known as popular snack among Indonesian. This kind of chips often associated with high uric acid level in the blood that is influenced by high level of purine. Therefore, an additional process is required to reduce purine content. It can increase acceptability and safety to consumer particularly for people with a previous history of hyperuricemia or gout. Objective : To determine and analyze the effect gamma ray irradiation on purin content of adenine and hypoxanthine including quuality properties of melinjo chips. Method : Research design apllied completely randomized design. Level of purin adenina and hypoxanthine analyzed using HPLC-UV. Chemical properties obtained using proximate analysis. In addition, hedonic sensory analysis test was applied in order to determine acceptability of the product. Result: Gamma ray irradiation conclusively can reduced purine base of adenine and hypoxanthine level approximately up to 17,82%. The higher dose of ray, the lower the purine level. Gamma ray effect significantly on the anorganic elements, fat, protein, and carbohydrate contents of the melinjo chips, along with its texture, appeareance and flavor. Conclusion : Irradiation reduced significantly purine base of adenine and hypoxanthine, nutritional content and organoleptic properties of melinjo chips. Keyword : Adenine; Gamma Ray; Gnetum gnemon L; Hypoxanthine; Irradiation